دور الموارد البشرية في تحقيق الكفاءة الإنتاجية دراسة ميدانية في الشركة العامة لصناعة الحراريات (المجلة العراقية للعلوم الاقتصادية, 2018)
The financial and human resources considred as one of the basic elements in the organization,. whatsoever either service or productive, and despite the importance of the financial resources of capital, machinery and machinery, but the human resources of the organization are more important than financiul physical resources where the organization owned skilled efficient human resources, make that organization to be able to perform its activities and business efficiently, and was able to achieve its objectives and messages. The efficiency of an organization measured by the possibility of exploiting all the resources . Where is the study of the role of human resources in the organization of the critical studies. to achieve the goals of the organization and increase its productivity efficienty . The research is divided into three sections first Section deals with the research methodology and second section contains the theoretical aspect of the importance of human resources and their goals to achieve production efficiencies. third section indicator the practical side that demonstrates the measure of productivity depending on the equation (indicator ) of the overall productivity of the company. The search reached some conclusious The most important Of them is conclusions that the company achieved high productivity and this due to back to the role of human resources in improving and increasing productivity .Research was presented several possible recommendations to be useful to the company.